General Equilibrium Analysis / A Microeconomic Text - Johnson Harry G; Krauss Melvyn B (Transaction Publishers, 2006)
The authors seek to introduce the student from the start to the general equilibrium approach to micro-economics, in the form of the two sector model. Preface, Assumptions and Introductory Concepts, Production and Distribution and General Equilibrium: Closed Economy, Exogenous Change in a Closed Economy, Policy-Induced Change in a Closed Economy, The Theory of Public Goods, The Theory of International Trade, The Theory of Tariffs, The Theory of Distortions, Exogenous Change in an Open Economy, The Theory of Economic Growth, References, Index.